Financial Literacy and Technology Advancement: Triggers of Gen Z's Crypto Investment Interest - Bintang Nurrama Putra; Ratnawati, Kusuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Cryptocurrency is gaining popularity among Generation Z, yet its complexity and volatility require strong financial understanding and technological access. This study aims to analyze the influence of financial literacy and technological advances on the interest in investing in cryptocurrency assets among Generation Z in Malang City. This explanatory quantitative study collected data from 153 respondents selected through purposive sampling, using questionnaires as the research instrument. The independent variables in this study are financial literacy and technological advances, while the dependent variable is interest in investing in cryptocurrency assets. The results of the analysis using Partial Least Squares – Structural Equation Modeling (PLS-SEM) show that both financial literacy and technological advances have a positive and significant effect on investment interest in cryptocurrency assets. These findings suggest that improved financial literacy and increased access to technology can encourage the younger generation to invest in digital assets. This research is expected to serve as a reference for financial institutions, regulators, and investment platform developers in designing educational strategies and developing digital-based financial technologies.